Ce‐exchange capacity of zeolite L in different cationic forms: a structural investigation. Issue 6 (25th November 2021) - Confalonieri, Giorgia; Vezzalini, Giovanna; Quattrini, Filippo; Quartieri, Simona; Dejoie, Catherine; Arletti, Rossella
Abstract : Zeolite L was Na‐ and NH4 ‐exchanged and the resulting samples were characterized by structural and chemical analyses. From the perspective of the possible use of zeolite L for rare earth element recovery (in particular Ce) and to unveil the differences in the affinity for Ce dictated by the presence of different counter‐cations, the three samples with LTL framework type were Ce 3+ ‐exchanged and fully characterized. Abstract : Cerium exchange by microporous materials, such as zeolites, has important applications in different fields, for example, rare earth element recovery from waste or catalytic processes. This work investigated the Ce‐exchange capacity of zeolite L in three different cationic forms (the as‐synthesized K form and Na‐ and NH4 ‐exchanged ones) from a highly concentrated solution. Chemical analyses and structural investigations allowed determination of the mechanisms involved in the exchanges and give new insights into the interactions occurring between the cations and the zeolite framework. Different cation sites are involved: (i) K present in the original LTL in the cancrinite cage (site KB) cannot be exchanged; (ii) the cations in KD (in the 12‐membered ring channel) are always exchanged; while (iii) site KC (in the eight‐membered ring channel) is involved only when K + is substituted by NH4 +, thus promoting a higher exchange rate for NH4 + → K + than for Na + → K + . In the Ce‐exchanged samples, a new site occupied by Ce appears in the centre of the main channel, accompanied by an increase in the number of and a rearrangement of H2 O molecules. In terms of Ce exchange, the three cationic forms behave similarly, from both the chemical and structural point of view (exchanged Ce ranges from 38 to 42% of the pristine cation amount). Beyond the intrinsic structural properties of the zeolite L framework, the Ce exchange seems thus also governed by the water coordination sphere of the cation. Complete Ce recovery from zeolite pores was achieved.